INTEGRATED POPULATION DATA RECORDING INFORMATION SYSTEM AT THE RT LEVEL BASED ON MOBILE (CASE STUDY IN CIROYOM CIKELET VILLAGE, GARUT REGENCY) - M Nandi Ginanjar (LKP Tematik Aperta Nusantara, 2026)
Population registration is an activity of data collection and recording of population events reports in order to issue population identity documents in the form of family cards and resident identification cards or other population documents issued by the local government. The population registration process is carried out in Ciroyom Cikelet Village, Garut Regency, precisely in Kp Rancaputat RT 03 / RW 04, population registration is still done manually using paper methods so that data is easily lost and damaged. Population registration here includes resident data according to family cards, current asset data and non-current asset data. The application consists of 4 parts: admin (Sensusu), residents, RT officers, The application was built with the aim of simplifying population data processing and providing population information, especially for residents around RT 03/RW 04 Ciroyom Village and making it easier for residents to apply for KTP cover letters. This Android-based application system was built with Microsoft Windows 10 Pro, the application creation process used Delphi 10.3 Rio Software with the Pascal Programming Language, MYSQL as the Database, and PHP MyAdmin as a tool for connecting Delphi Software and MYSQL. Based on the results of the tests that have been carried out, the application runs well.